Perbandingan Sistem Hukum Inggris Dengan Jerman (Refleksi Terhadap Sumber Hukum Dan Penerapan Hukum Indonesia) - Manotar Tampubolon; Putu George Matthew Simbolon (Fakultas Hukum Universitas Islam Malang, 2022)
This article explains the differences and similarities between the British legal system and German Law and reflects their application to Indonesian law which was influenced by the swift flow of legalism. The writing uses a normative juridical method with a comparative law approach. Authors use English common law sources along with their application and German civil law along with their application under the stuffenbau theory. The difference between these legal systems is the common law system prioritizes precedent application, while the civil law system prioritizes statutes. Furthermore, these systems also have similarities whereas both systems are applying customs, doctrines, and legal interpretations as to their complementary legal instruments. The authors address that Indonesia needs to apply methods beyond the statute approach, and Indonesia shall take into account customs, doctrines, and interpretations to achieve justice.